MODERN WESTERN EUROPEAN EXPERIENCE OF CORPORATE SOCIAL RESPONSIBILITY - Elena Smirnova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the modern Western European experience of corporate social responsibility. On the example of Germany, UK, Austria and Sweden various directions of the development and public recognition of socially responsible business practice were demonstrated.